Big Data Analysis Model for MRO Business Using Artificial Intelligence System Concept - JUNG, Inhwan; SUN, He; KANG, Jangmook; Hyong Lee, Choong; LEE, Sangwon (International Journal of Engineering and Technology, 2018)
The rapidly changing environment of the shipbuilding industry has put Koreaâ€™s shipbuilding industry in a crisis. The purpose of this study was to develop a business model to maintain, maintain and operate Big Data-based MRO(Maintenance, Repair, and Operation) consumables, which is expected to be the new growth engine for the domestic shipbuilding industry. Although Korean shipbuilders have world-class technologies for ship dogma, the market for ship maintenance and repair is still in its infancy. For Korean shipbuilders, MRO business can be a growth engine that will provide food for the next 30 years, but to do so, we need to make sure that everything that happens in the entire process, from ship design to maintenance and maintenance. Therefore, by systematically establishing Big Data related to components and developing MRO business models based on data analysis capabilities using Artificial Intelligence system concept, we can develop new growth engines for related industries in Ship Industry.Â Â